THE EFFECT OF RELIGIOSITY AND ACADEMIC RESILIENCE ON DECREASE IN THE LEVEL OF ACADEMIC ANXIETY OF MASTER STUDENTS OF ISLAMIC EDUCATION, STATE ISLAMIC UNIVERSITY OF SULTAN SYARIF KASIM RIAU - Priti Ike Jelita Priti (PT. Jurnal Center Indonesia Publisher, 2025)
This study aims to analyze the influence of religiosity and academic resilience on decreasing the level of academic anxiety of students of the Master of Islamic Education Program at the Sultan Syarif Kasim State Islamic University, Riau. Academic anxiety is a common psychological challenge experienced by postgraduate students. Religiosity and academic resilience are seen as protective factors that can help students manage academic stress in a healthier way. This study uses a quantitative method with data collection techniques in the form of questionnaires and documentation. The research sample consisted of 41 students from three semesters selected through purposive sampling. Data analysis was carried out using the independent sample t-test using SPSS version 25. The results showed that religiosity had a significant effect on academic anxiety with a significance value of 0.029, while academic resilience showed a stronger effect with a significance value of 0.000. Because the significance results of both variables are less than 0.05, the higher the religiosity and academic resilience of students, the lower their level of academic anxiety. This finding confirms that the integration of the values ​​of religiosity and resilience is very important in supporting students' mental resilience. Strengthening religiosity and fostering academic resilience can be effective strategies to reduce academic anxiety in postgraduate higher education.